2014
DOI: 10.2304/rcie.2014.9.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers' Views of Children's and Adults' Play in Japan, Taiwan, and the USA

Abstract: Teachers' perspectives of play differ widely because of social and cultural influences that can be seen in their values and beliefs about play in different countries. In a global community, sharing educators' knowledge of play and their perspectives of how to educate children through the use of play would be appropriate and complementary in understanding early childhood education in different countries. To understand the meaning of play, American, Japanese and Taiwanese early childhood preservice teachers' per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Some cross-cultural studies of American and Japanese educators' perceptions of play (Izumi-Taylor et al, 2014;Izumi-Taylor et al, 2010b;Izumi-Taylor et al, 2004) found Japanese teachers consider play as the way to promote children's social development more than their American counterparts.…”
Section: Japanese and American Teachers' Views Of Playmentioning
confidence: 99%
See 4 more Smart Citations
“…Some cross-cultural studies of American and Japanese educators' perceptions of play (Izumi-Taylor et al, 2014;Izumi-Taylor et al, 2010b;Izumi-Taylor et al, 2004) found Japanese teachers consider play as the way to promote children's social development more than their American counterparts.…”
Section: Japanese and American Teachers' Views Of Playmentioning
confidence: 99%
“…Despite differences in political, educational, and religious systems, American and Japanese educators consider play important in children’s learning and development (Izumi-Taylor et al, 2014; Izumi-Taylor et al, 2010b); yet, it is inappropriate to assume “that adult recollections about play will be helpful in understanding play in the elementary school from the children’s perspectives” (King, 1986: 233). Viewing children’s play perspectives through PEIs might help educators understand the best way to comprehend children’s definitions of play.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations